Modelling an energetic tidal strait: investigating implications of common numerical configuration choices. (March 2021) - Mackie, Lucas; Evans, Paul S.; Harrold, Magnus J.; O`Doherty, Tim; Piggott, Matthew D.; Angeloudis, Athanasios
Highlights: Variable friction based on seabed morphology aids hydrodynamic model calibration. High mesh refinement required to capture small but influential bathymetric features. Implications of these model configurations for tidal energy developments are discussed Abstract: Representation of the marine environment is key for reliable coastal hydrodynamic models. This study investigates the implications of common depth-averaged model configuration choices in sufficiently characterising seabed geometry and roughness. In particular, applications requiring a high level of accuracy and/or exhibiting complex flow conditions may call for greater detail in marine environment representation than typically adopted in coastal models. Ramsey Sound, a macrotidal strait in Pembrokeshire, Wales, UK is considered as a case study. The site contains various steeply inclined bathymetric features, including a submerged pinnacle named Horse Rock and a rocky reef called "The Bitches". The available energy in Ramsey Sound's tidal currents has attracted attention from tidal energy developers. There is interest in accurately modelling the energetic hydrodynamics surrounding its pronounced bathymetry. The coastal flow solver Thetis is applied to simulate the flow conditions in Ramsey Sound. It is shown that notable prominent bathymetric features in the strait influence localised and, most importantly, regional hydrodynamic characteristics. "The Bitches" consistently accelerate flow in the strait while Horse Rock induces a notable wake structure and flow reversals. The model is calibrated against bed- and vessel-mounted Acoustic Doppler Current Profiler (ADCP) observations, by altering seabed roughness parameterisations. A spatially variable and locally scaled Manning coefficient based on diverse seabed classification observations is found to improve model performance in comparison to uniformly applied constants, the latter a more common approach. The local impact of altering the Manning coefficient configuration is found to be greatest during spring flood periods of high velocity currents. Meanwhile, the effect of coarsening the computational mesh around bathymetric features towards values more typically applied in coastal models is investigated. Results indicate severe misrepresentation of seabed geometry and subsequent wake hydrodynamics unless refined to a mesh element size that adequately represents Horse Rock and "The Bitches".